Defensive Medicine in U.S. Spine Neurosurgery. Issue 3 (February 2017) - Din, Ryan S.; Yan, Sandra C.; Cote, David J.; Acosta, Michael A.; Smith, Timothy R.
Abstract : Study Design: Observational cross-sectional survey. Objective: To compare defensive practices of U.S. spine and nonspine neurosurgeons in the context of state medical liability risk. Summary of Background Data: Defensive medicine is a commonly reported and costly phenomenon in neurosurgery. Although state liability risk is thought to contribute greatly to defensive practice, variation within neurosurgical specialties has not been well explored. Methods: A validated, online survey was sent via email to 3344 members of the American Board of Neurological Surgeons. The instrument contained eight question domains: surgeon characteristics, patient characteristics, practice type, insurance type, surgeon liability profile, basic surgeon reimbursement, surgeon perceptions of medical legal environment, and the practice of defensive medicine. Results: The overall response rate was 30.6% (n = 1026), including 499 neurosurgeons performing mainly spine procedures (48.6%). Spine neurosurgeons had a similar average practice duration as nonspine neurosurgeons (16.6 vs 16.9 years, P  = 0.64) and comparable lifetime case volume (4767 vs 4, 703, P  = 0.71). The average annual malpractice premium for spine neurosurgeons was similar to nonspine neurosurgeons ($104, 480.52 vs $101, 721.76, P  = 0.60). On average, spine neurosurgeons had a significantly higher rate of ordering labs, medications, referrals, procedures, and imaging solely for liability concerns compared with nonspine neurosurgeons (89.2% vs 84.6%, P  = 0.031). Multivariate analysis revealed that spine neurosurgeons were roughly 3 times more likely to practice defensively compared with nonspine neurosurgeons (odds ratio, OR = 2.9, P  = 0.001) when controlling for high-risk procedures (OR = 7.8, P  < 0.001), annual malpractice premium (OR = 3.3, P  = 0.01), percentage of patients publicly insured (OR = 1.1, P  = 0.80), malpractice claims in the last 3 years (OR = 1.13, P  = 0.71), and state medical-legal environment (OR = 1.3, P  = 0.37). Conclusion: State-based medical legal environment is not a significant driver of increased defensive medicine associated with neurosurgical spine procedures. Level of Evidence: 3